Rapid detection of ampicillin resistance in Escherichia coli by quantitative mass spectrometry - Grundt, Alexander; Findeisen, Peter; Miethke, Thomas; Jäger, Evelyn; Ahmad-Nejad, Parviz; Neumaier, Michael (Journal of clinical microbiology, 2012)
Early targeted antimicrobial therapy helps saving costs and prevents the spread of antimicrobial resistances including in Escherichia coli, the most frequent gram-negative bacterium causing sepsis. Therefore, rapid susceptibility testing represents the major prerequisite for knowledge-based successful antimicrobial treatment. To accelerate testing for antibiotic susceptibility, we have developed a new mass spectrometry-based assay for antibiotic susceptibility testing (MAAST). For proof of principle we present an ampicillin susceptibility test for E.coli with a TAT of 90 minutes upon growth detection.